Performance Analysis of Space-to-Ground Downlink for Polarization Shift Keying Optical Communications with a Gaussian-Schell Model Beam - Jiajie Wu; Yuwei Zhang; Qingyan Li; Siyuan Yu; Jianjie Yu (Photonics)
Free-space optical communication has emerged as a pivotal technology for space-to-ground downlinks; however, signal degradation caused by atmospheric turbulence continues to pose a significant challenge. In this study, a model for the polarization transmission characteristics of a Gaussian-Schell model (GSM) beam in downlink was established, and conditions sufficient for maintaining the polarization transmission characteristics were derived. The impact of the source spatial coherence on the performance of optical communication systems using circular polarization shift keying (CPolSK) modulation was investigated. Additionally, models for the probability density distribution and scintillation index of the optical intensity under atmospheric turbulence were developed along with a bit error rate model for the optical communication system. The effects of the laser spatial coherence on these models were also analyzed. The results indicate that the optimal performance in the turbulent downlink is achieved with fully coherent light, where the GSM-beam-based CPolSK-modulated system demonstrates a reduction of 1.51 dB in the required power compared to that of an on–off keying system. The implications of this study suggest that optimizing spatial coherence could significantly enhance the reliability of space-to-ground communication systems under atmospheric disturbances.